The role of self-management for government school leaders with the participation of teachers in decision-making in light of the Corona pandemic form their viewpoint in Mafraq Governorate - Elshrafat, Diab Ghassab Fazi (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the role of self-management for public school leaders, with the participation of teachers in decision-making during the Corona pandemic in Mafraq Governorate from their point of view, and to identify the impact of variables (educational stage and years of experience) on the responses of the study sample members towards the role of self-management for government school leaders with the participation of Teachers in decision making. The study used the descriptive analytical approach, and the study sample consisted of (396) male and (801) female teachers in Mafraq Governorate schools, and the SPSS statistical package program was used to analyze and interpret the data. The results of the study concluded that the arithmetic mean of the granted powers field came to a medium degree and an arithmetic average (3.17%), and that the field of professional development for teachers came to a medium degree and an arithmetic average (3.37%), and the educational accounting field came to a medium degree and an arithmetic average (2.95%), while the field of educational accounting came to a medium degree and an arithmetic average (2.95%), while the field of educational accounting came to a medium degree and an arithmetic average Communication and Information Technology came to a medium degree, with an arithmetic average (3.29%).